2016
DOI: 10.5194/acp-16-12875-2016
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the chemical composition of the submicron aerosol and in the sources of the organic fraction at a regional background site of the Po Valley (Italy)

Abstract: Abstract. Fine particulate matter (PM) levels and resulting impacts on human health are in the Po Valley (Italy) among the highest in Europe. To build effective PM abatement strategies, it is necessary to characterize fine PM chemical composition, sources and atmospheric processes on long timescales (> months), with short time resolution (< day), and with particular emphasis on the predominant organic fraction. Although previous studies have been conducted in this region, none of them addressed all these… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 97 publications
8
30
0
Order By: Relevance
“…On the multi-year basis of the project, OA represents on average 45 ± 8 % (33 %-58 %) and 46 ± 7 % (36 %-50 %) of the total non-refractory submicron particles (PM 1 -NR) at the urban and rural sites, respectively, within the range reported in the literature for other European sites and the Asian regions (Hu et al, 2017;Li et al, 2015;Wu et al, 2018, for China and East Asia;Chakraborty et al, 2018, for India), and slightly less than the values reported for the southeastern US (50 %-75 %, Xu et al, 2015;Budisulistiorini et al, 2016). Among this fraction, primary sources (POA) are dominated by biomass burning (23 ± 13 %), especially at the rural site (SPC), whereas the fossil fuel combustion (12 ± 7 %) is higher at the urban background site (Bologna), where it also presents a marked seasonality.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…On the multi-year basis of the project, OA represents on average 45 ± 8 % (33 %-58 %) and 46 ± 7 % (36 %-50 %) of the total non-refractory submicron particles (PM 1 -NR) at the urban and rural sites, respectively, within the range reported in the literature for other European sites and the Asian regions (Hu et al, 2017;Li et al, 2015;Wu et al, 2018, for China and East Asia;Chakraborty et al, 2018, for India), and slightly less than the values reported for the southeastern US (50 %-75 %, Xu et al, 2015;Budisulistiorini et al, 2016). Among this fraction, primary sources (POA) are dominated by biomass burning (23 ± 13 %), especially at the rural site (SPC), whereas the fossil fuel combustion (12 ± 7 %) is higher at the urban background site (Bologna), where it also presents a marked seasonality.…”
Section: Discussionsupporting
confidence: 77%
“…However, the biomass burning contribution to POA remains the most important source of POA also at the urban site during the cold fall/winter seasons. The BBOA contribution ranging from 17 % to 38 % at Bologna during the fall/winter seasons is not far from the values reported for other European cities (10 %-40 % in Paris, Crippa et al, 2013b; 5 %-27 % from the EUCAARI multi-site study, Crippa et al, 2014) and United States areas (e.g., 15 %-33 % for the southeastern US, Budisulistiorini et al, 2016), and slightly higher than that of other highly populated and polluted cities/regions of Asia (11 %-14 % at Beijing, China, Sun et al, 2018;10 %-20 % at Kunpur, India, Chakraborty et al, 2018), where, however, other combustion sources (i.e., coal) contribute to the POA fraction.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In general, wintertime studies have shown lower total concentrations of submicron aerosols than summer. Similar to summer studies, OA is a major (and often the largest) fraction of submicron aerosol in the winter, typically with increases in primary OA (POA), mostly driven by increases in biomass burning OA (BBOA) from residential wood burning (Bressi et al, 2016;Budisulistiorini et al, 2016;Crippa et al, 2013;Lanz et al, 2008;Xu et al, 2015Xu et al, , 2016. The amount of oxidized OA (OOA) observed in warmer months of the year has been documented extensively in the literature, throughout much of the world (Jimenez et al, 2009, and references within).…”
Section: Introductionmentioning
confidence: 95%
“…Although heavy pollution episodes can occur also on the French side of the Alps (e.g. Chazette et al, 2005;Brulfert et al, 2006;Bonvalot et al, 2016;Chemel et al, 2016;Sabatier et al, 2018), it is very rare to clearly spot an aerosol layer transported from that region to Aosta, since in those cases air masses coming from the west must have crossed the Alps and are almost always mixed with clean air from the uppermost layers; therefore, only a dim aerosol backscatter signal is usually noticed from the ALC.…”
Section: Daily Classification Schemes Based On Alc Measurements or Mementioning
confidence: 99%